(untitled) (The Research of Medical Science Review, 2025)
Introduction: These days psychological problems are rising in our society. Minute changes in the skin result in a serious emotional state. Acne vulgaris is one of the most common skin diseases in this region. Objective: This study aimed to determine the frequency of depression in patients with acne vulgaris. Methodology: This Cross-sectional study was conducted at the OPD of the Dermatology Department, LNH during April 06 2023 to Oct 06 2023. A total of 150 patients who presented at the OPD of the Dermatology Department, LNH, meeting the eligibility criteria were included in the study. Frequency and percentage were calculated for gender, smoking (yes/no), alcohol consumption (yes/no), educational status, marital status, residential status, income status, occupational status, acne severity, and the presence of depression (yes/no). Results: Of the 150 patients, 61 (40.6%) were males and 89 (59.3%) were women. The mean age of the patients was 33.4 ± 7.60 years and mean duration of disease was 12 ± 6 months. Of the total number of patients with acne vulgaris, 94 (62.8%) had a moderate form of acne and the remaining patients were equally distributed between the mild and severe acne groups 28 (18.6%). Of 150 patients with acne vulgaris, 90 (60%) had depression. Conclusion: A high incidence of depression in the patients with acne vulgaris has been found in the current study, which is related to age group and other factors also. Long-term psychometric assessments are essential for the management of acne vulgaris.